1996
DOI: 10.1007/bf00019555
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cysteine and serine proteases during xylogenesis in Zinnia elegans

Abstract: The terminal process of xylogenesis, autolysis, is essential for the formulation of a tubular system for conduction of water and solutes throughout the whole plant. Several hydrolase types are implicated in autolysis responsible for the breakdown of cytoplasm. Here, we characterize p48h-17 cDNA from in vitro tracheary elements (TEs) of Zinnia elegans which encodes a preproprotein similar to papain. The putative mature protein, a cysteine protease, has a molecular mass of 22,699 Da with a pI of 5.7. DNA gel blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 52 publications
7
85
1
2
Order By: Relevance
“…Protease synthesis and proteosome activity have been associated with secondary cell wall development (16)(17)(18), and there is evidence for budding or vesiculation of the nucleus and the cytoplasm in Zinnia and pine TEs (19,20); vesicular removal of cell contents is a prime feature of mammalian cell apoptosis. Although there is no information on specific chromatin changes in the process (2), some elements of DNA repair also occur (1).…”
mentioning
confidence: 99%
“…Protease synthesis and proteosome activity have been associated with secondary cell wall development (16)(17)(18), and there is evidence for budding or vesiculation of the nucleus and the cytoplasm in Zinnia and pine TEs (19,20); vesicular removal of cell contents is a prime feature of mammalian cell apoptosis. Although there is no information on specific chromatin changes in the process (2), some elements of DNA repair also occur (1).…”
mentioning
confidence: 99%
“…the reaction was stopped immediately without further incubation and without substrate. One unit of proteolytic activity in 1 cm cuvette was defined as an increment of 0.01 in A340 in 1 h. For inhibitor studies, the reaction mixture containing 50 μl of the crude extract was preincubated for 10 min with one of the following inhibitors −3.8 μl of 2 mM PMSF, 18.8 μl of 10 mM EDTA, 9.4 μl of 25 μM DL-norleucine and 3.8 μl of 10 mM iodoacetamide for serine-, metallo-, aspartate-, and cysteine proteases, respectively (Ye and Varner 1996). The remaining procedure was the same as for the endopeptidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a serine protease of 145 kD was detected specifically in differentiating TEs on substrate-impregnated gels (Beers and Freeman, 1997). An approximately 60 kD serine protease was also reported to appear preferentially in TE-inducing culture (Ye and Varner, 1996;Beers and Freeman, 1997). The activity of the 60 kD protease is higher above pH 7, which is unlike the pH optimum of the autolysis-specific cysteine protease, suggesting that at least two compartments with different pHs are involved in the autolysis.…”
Section: Autolysismentioning
confidence: 99%
“…Organellar degeneration is coupled with a high activity of proteases (Minami and Fukuda, 1995;Ye and Varner, 1996;Beers and Freeman, 1997). Single-cell protease assay has indicated that differentiating TEs themselves have high proteolytic activities, which suggests cellautonomous protein degradation in TEs (Beers and Freeman, 1997).…”
Section: Autolysismentioning
confidence: 99%